Church silver in the monetary reform of 1922-1924 years - Ivanov Sergei, deacon (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article oﬀers support the claim expense seized in 1922 under the slogan of helping the starving of church property in the minting of coins in connection with the monetary reform. It is primarily a silver, whose share in the value of the selected property in the existing temples was 86 percent. Need dragmetalah as the reform of the circulation of money there, regardless of the problem of hunger 1921–1922 and determined refusal of the Bolshevik leaders from the course on monetary economy in the post-war chaos. Evidence for the main thesis of the article served as the internal reports of structural divisions of People’s Commissariat of Finance and the People’s Commissariat of Workers ‘and Peasants’ Inspection, which indicated that in the period of the campaign for the withdrawal and delivery of church property in the state store, recently seen as the main source of silver for coinage on Petrograd Mint. Information about church silver was present in the reports to send to the metal from Gokhran Mint statements and the amount of metal intended for coinage. Demand for silver for the execution of production programs for minting exceed the available reserves of the metal, which resulted in the purchase of silver on foreign markets and buying coins Imperial coinage in the population of the country. Silver in donations and reform played a role supportive factor for strengthening conﬁdence in the paper currency treasury.